Proceedings of the Genetic and Evolutionary Computation Conference Companion 2022
DOI: 10.1145/3520304.3534004
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of genetic improvement tools for improvement of non-functional properties of software

Abstract: Genetic improvement (GI) improves both functional properties of software, such as bug repair, and non-functional properties, such as execution time, energy consumption, or source code size. There are studies summarising and comparing GI tools for improving functional properties of software; however there is no such study for improvement of its non-functional properties using GI. Therefore, this research aims to survey and report on the existing GI tools for improvement of non-functional properties of software.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…GI tool Recent survey of GI tooling, revealed that [13] few GI tools can be easily applied to unseen software. After closer investigation we chose Gin [4], as it is the only one to implement fitness functions for at least two non-functional software properties, namely runtime and memory consumption.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…GI tool Recent survey of GI tooling, revealed that [13] few GI tools can be easily applied to unseen software. After closer investigation we chose Gin [4], as it is the only one to implement fitness functions for at least two non-functional software properties, namely runtime and memory consumption.…”
Section: Methodsmentioning
confidence: 99%
“…In fact finding more memory efficient versions of software can be beneficial to it's speed by saving expensive garbage collection and page swapping operations. Although multiobjective search algorithms seem best fit for this problem domain, to the best of our knowledge, there is no tool available that provides this facility, despite such work being proposed in the past [13].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly Gabin An [1] proposed PyGGI for Python. Nevertheless recently a user study said that GI lacked user friendly tools [12]. To address this Magpie [2] was released last year as an open source project.…”
Section: Genetic Improvement With Magpiementioning
confidence: 99%